2002
DOI: 10.1002/prot.10149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidic phospholipids on the structural properties of recombinant cytosolic human glyoxalase II

Abstract: A peculiar characteristic of highly concentrated cytosolic recombinant human glyoxalase II (GII) solutions is to undergo partial precipitation. Previous work indicated that anionic phospholipids (PLs) exert a noncompetitive inhibition on the enzymatic activity of the soluble enzyme. In this study, FTIR spectroscopy was used to analyze the structural properties and the thermal stability of the soluble protein in the absence and in the presence of liposomes made of different phospholipids (PLs). The structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…These data are in agreement with the experiments of differential scanning calorimetry showing that the temperature of melting ( T m ) of this enzyme was 108°C 28. Thermal denaturation curves for Ssβ‐gly and Taβ‐gly were obtained by plotting the changes of the amide I′ bandwidth as a function of the temperature29, 30 (data not shown). The temperature of melting for Ssβ‐gly and Taβ‐gly resulted 98.1 and 98.4°C, respectively and was calculated as described 18…”
Section: Resultssupporting
confidence: 87%
“…These data are in agreement with the experiments of differential scanning calorimetry showing that the temperature of melting ( T m ) of this enzyme was 108°C 28. Thermal denaturation curves for Ssβ‐gly and Taβ‐gly were obtained by plotting the changes of the amide I′ bandwidth as a function of the temperature29, 30 (data not shown). The temperature of melting for Ssβ‐gly and Taβ‐gly resulted 98.1 and 98.4°C, respectively and was calculated as described 18…”
Section: Resultssupporting
confidence: 87%
“…The amide II band intensity (absorption close to 1550 cm −1 ) is very sensitive to 1 H/ 2 H exchange. A large decrease in amide I band intensity reflects a high protein flexibility and/or a low compact structure 35–38. The infrared spectra of KRAB‐A and KRAB‐AB analyzed in 2 H 2 O medium at 20°C showed a very low absorption close to 1550 cm −1 (data not shown) that did not decrease significantly at high temperatures (data not shown), indicating that at 20°C the 1 H/ 2 H exchange was complete, and suggesting, in turn, a highly flexible protein structure 35–38…”
Section: Resultsmentioning
confidence: 96%
“…These spectra (Fig. 5) show that, with the increase in temperature, the intensity of the amide I′ band decreases while the intensity of the bands close to 1615 and 1682 cm −1 (aggregation bands) increases, reflecting denaturation and aggregation, respectively 37. Hence, the denaturation and aggregation process may be followed by plotting the ratio between the intensity of the amide I′ band and the intensity of the 1615 cm −1 aggregation band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in peak intensity corresponding to (101) crystal plane indicated that the growth of ZnO flakes was preferentially oriented towards (101) crystal plane. [41] and b sheets of GLO 1 [42,43] respectively. The last peak confirmed the immobilization of GLO 1 with ZnO flakes.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%